A High-Voltage Gain Non-Isolated DC–DC Converter Designed for Bipolar DC Microgrids. Issue 12 (21st July 2023) - Fernão Pires, Vitor; Cordeiro, Armando; Foito, Daniel; Silva, José Fernando
Abstract: DC microgrids are now starting to attract huge attention from researches and engineers. Among the several DC microgrid architectures, bipolar DC microgrids are advantageous to accommodate a wider range of DC loads. However, due to mismatched loads connected to the two poles, bipolar DC microgrids may show voltage balancing issues. In this context, this article presents a new high input-to-output voltage gain, non-isolated DC–DC converter specifically designed for bipolar DC Microgrids. The proposed converter supports the balance of voltages at both bipolar DC microgrid poles, as the converter can transfer energy between the two poles in an unbalanced way. The description, theoretical support, and operation of the proposed converter will be presented. The theoretical assumptions will be complemented with several results obtained from computer simulation tests. The simulation tests will be compared to laboratory results from an experimental prototype. The obtained results confirm the theoretical properties of the proposed converter.